A method for preparing super absorbent core-sheath structure nanofibers using three-stage coaxial electrospinning
Through three-stage coaxial electrospinning technology and electrospinning process, superwater-absorbent core sheath structure nanofibers were prepared, solving the problems of complex preparation methods of existing superwater-absorbent fibers and low water absorption performance, achieving low-cost and efficient nanofiber preparation, with good application prospects.
Patent Information
- Application Number
- CN202310290672.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-23
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-03-23
AI Technical Summary
The existing superabsorbent fiber preparation methods are complex, with large fiber diameters and low water absorption performance, and require post-treatment such as polymerization and cross-linking after spinning.
Three-stage coaxial electrospinning technology is used to prepare a clear and transparent polymer solution by magnetic stirring, and the electrospinning process is used to prepare the solutions of polystyrene, polyacrylic acid and polycaprolactone as solutions of the core layer, intermediate layer and sheath layer respectively to prepare nanofibers with super-water absorption properties.
The prepared superwater-absorbent core sheath structure nanofibers are cheap, have good water absorption performance and controllability, no post-treatment, simple process, suitable for a variety of polymer replacement, and have good application prospects.
Smart Images

Figure CN116219560B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nanofibers, and in particular relates to a method for preparing super absorbent core-sheath structure nanofibers by using three-stage coaxial electrospinning. Background Art
[0002] The existing methods for preparing super absorbent fibers are mostly traditional solution spinning and melt spinning, and the fiber diameters are mostly in the micron range. The main disadvantages of traditional solution spinning and melt spinning include: the dry spinning technology is difficult and the production cost is high; the wet spinning process is complicated and the spinning speed is low; the continuity of the dry and wet spinning process is poor; the melt spinning has high requirements for polymers, etc. In addition, the preparation process of some super absorbent fibers requires further modification of the fibers after spinning, so the preparation process is relatively cumbersome. Compared with these shortcomings, the electrospinning method has a simple device, low cost, a wide variety of spinnable types, and a controllable process. It has become one of the main methods for effectively preparing nanofiber materials. With the development of electrospinning technology, it has become possible to simultaneously process multiple working fluids, regulate the composition and structure of the substrate, and prepare functional nanofibers with complex structures in one step.
[0003] The existing patents for preparing super absorbent fibers mainly include: Patent No. CN115595794A of Guangdong Bidifu Medical Technology Co., Ltd., which uses polypropylene as raw material, and prepares polypropylene fiber as a supporting core layer through spunbonding or melt spinning process. Ultraviolet induced free radical polymerization reaction causes acrylic acid to grow and polymerize on the surface of polypropylene fiber to form a super absorbent cortex, thereby obtaining super absorbent fiber with high mechanical properties.
[0004] Chinese patent application CN1664189A discloses a super absorbent fiber process, which uses an acrylic copolymer blend to first form a polymer solution, and then dry-spin and thermally cross-link to obtain super absorbent fibers. The preparation methods in the above two patents are more complicated and cumbersome than the preparation process of the present invention, and require polymerization, cross-linking and other post-treatments after spinning to obtain super absorbent fibers, and the fiber diameter is larger and the water absorption performance is lower. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing super absorbent core-sheath structure nanofibers using three-stage coaxial electrospinning, characterized in that it comprises the following steps:
[0006] S1: weigh chloroform and N,N-dimethylformamide and add them into a first screw-mouth conical flask, then weigh dry polystyrene particles and add them into the first screw-mouth conical flask, and finally stir with a magnetic stirrer to obtain a clear, transparent and uniform first polymer solution, which is set aside for later use;
[0007] S2: weigh chloroform and N,N-dimethylformamide and add them into a second screw-mouth conical flask, then weigh polyacrylic acid powder and add it into the second screw-mouth conical flask, and finally stir with a magnetic stirrer to obtain a clear, transparent and uniform second polymer solution;
[0008] S3: weighing chloroform and N,N-dimethylformamide and adding them into a third screw-mouth conical flask, then weighing polycaprolactone particles and adding them into the third screw-mouth conical flask, and finally stirring with a magnetic stirrer to obtain a clear, transparent and uniform third polymer solution;
[0009] S4: A three-stage coaxial electrospinning process was used. A syringe was used to collect the first polymer solution, the second polymer solution and the third polymer solution respectively. The first polymer solution, the second polymer solution and the third polymer solution were placed in the propulsion pumps of the core layer, the middle layer and the sheath layer respectively. A cardboard box wrapped in aluminum foil was used as a receiver to spin nanofibers with super absorbency.
[0010] Furthermore, in S1-S3, 10-40 mL of chloroform and N,N-dimethylformamide are respectively measured, and the weighed masses of polystyrene, polyacrylic acid and polycaprolactone are all 0.5-5.0 g.
[0011] Furthermore, in S1, 20 mL and 30 mL of chloroform and N,N-dimethylformamide were measured respectively; in S2, 15 mL and 35 mL of chloroform and N,N-dimethylformamide were measured respectively; in S3, 40 mL and 10 mL of chloroform and N,N-dimethylformamide were measured respectively; in S1-S3, the weighed masses of polystyrene, polyacrylic acid and polycaprolactone were all 0.5-2.0 g.
[0012] Furthermore, in S1-S3, the magnetic rotor is placed in a screw-mouth conical flask, and the screw-mouth conical flask is placed on a magnetic stirrer for stirring, and the stirring time is 12-24 hours.
[0013] Furthermore, the stirring time is 20-24h.
[0014] Furthermore, in S4, the electrospinning process is specifically as follows: the positive electrode of the high-voltage power supply is connected to the needle of the coaxial spinning head, the negative electrode is connected to the aluminum foil, the parameters of the spinning flow rate, the spinning voltage and the receiving distance are set, the high-voltage power supply is turned on and spinning is performed to obtain nanofibers with super water absorbency.
[0015] Furthermore, the spinning flow rates are as follows: the core layer flow rate is set to 0.5-2.5 mL / h, the middle layer flow rate is set to 0.3-2.0 mL / h, and the sheath layer flow rate is set to 0.5-1.2 mL / h; the spinning voltage is 6.0-9.0 KV; and the receiving distance is 14-18 cm.
[0016] Furthermore, the core layer flow rate is 1.0-2.0 mL / h, the middle layer flow rate is 0.3-1.0 mL / h, and the sheath layer flow rate is 0.5-1.0 mL / h; the spinning voltage is 7.0-8.5 KV; and the receiving distance is 16-18 cm.
[0017] Furthermore, super absorbent core-sheath structure nanofibers are prepared, and the core-sheath structure includes a core layer, an intermediate layer and a sheath layer. The first polymer solution, the second polymer solution and the third polymer solution are used as solutions for the core layer, the intermediate layer and the sheath layer, respectively. In the prepared super absorbent core-sheath structure nanofibers, the intermediate layer made of polyacrylic acid has super absorbency and is used to absorb liquid, the core layer made of polystyrene is used to provide the required rigidity of the fiber and maintain the fiber morphology characteristics, and the sheath layer made of polycaprolactone protects the fiber structure to prevent the fiber membrane from shrinking into a ball due to excessive water absorption by the intermediate layer.
[0018] Compared with the prior art, the beneficial effects of the present invention are mainly reflected in:
[0019] 1. The super absorbent core-sheath structure nanofibers prepared by the present invention are low-cost, and the polymers used in the core layer, the middle layer and the sheath layer of the super absorbent core-sheath structure nanofibers can be replaced by other suitable polymers, and the polymer selection is diverse.
[0020] 2. The super absorbent core-sheath structure nanofibers prepared by the present invention not only have the effect of absorbing a large amount of liquid, but also can maintain the fiber membrane morphology after absorbing water; the process flow is simple, the fiber morphology is controllable and no post-treatment is required, and it has a good application prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a schematic diagram of the preparation of super absorbent core-sheath structure nanofibers using three-stage coaxial electrospinning in the present invention.
[0022] Figure 2 This is a transmission electron micrograph of the super absorbent core-sheath structure nanofiber prepared in the present invention.
[0023] Figure 3 Schematic diagram of the absorption performance of deionized water by the super absorbent core-sheath structure nanofibers prepared in the present invention. DETAILED DESCRIPTION
[0024] The following is a more detailed description of a method for preparing super absorbent core-sheath structured nanofibers using three-stage coaxial electrospinning in conjunction with a schematic diagram, which shows a preferred embodiment of the present invention. It should be understood that those skilled in the art can modify the present invention described herein and still achieve the beneficial effects of the present invention. Therefore, the following description should be understood as being widely known to those skilled in the art and not as a limitation to the present invention.
[0025] like Figure 1As shown, a method for preparing super absorbent core-sheath structure nanofibers using three-stage coaxial electrospinning comprises the following steps:
[0026] Step 1, adding 0.5-5.0 g of polystyrene (PS) particles into a mixed solvent of chloroform (TCM) and N,N-dimethylformamide (DMF), stirring on a magnetic stirrer to obtain a clear and transparent polymer solution for later use;
[0027] Step 2: Add 0.5-5.0 g of polyacrylic acid (PAA) powder into a mixed solvent of trichloromethane (TCM) and N,N-dimethylformamide (DMF), stir on a magnetic stirrer to obtain a clear and transparent polymer solution for later use;
[0028] Step 3, adding 0.5-5.0 g of polycaprolactone (PCL) particles into a mixed solvent of trichloromethane (TCM) and N,N-dimethylformamide (DMF), stirring on a magnetic stirrer to obtain a clear and transparent polymer solution for later use;
[0029] Step 4: Using a three-stage coaxial electrospinning process, each polymer solution is prepared into a nanofiber membrane with super water absorption performance.
[0030] In order to further illustrate the technical solution of the present invention, the preferred embodiments of the present invention are described below in conjunction with examples.
[0031] Three-stage coaxial electrospinning means pouring the spinning solutions corresponding to the core layer (support layer), the middle layer (water absorbing layer), and the sheath layer (protective layer) into three syringes respectively, placing the syringes in the syringe pump, and the syringe pump pushes the liquid at a certain rate, and at the same time connects the high-voltage electrostatic generator to the spinning needle with a three-stage coaxial structure for electrostatic spinning, and the electrospun fibers are collected on aluminum foil to obtain core-sheath structure nanofibers. The micro-injection pump used in the experiment is the micro-injection pump production KDS100 / KDS200, the high-voltage electrostatic generator for electrospinning is ZGF60kV / 2mA produced by Wuhan Huatian Electric Power Automation Co., Ltd., and the magnetic stirrer is 81-2 produced by Shanghai Sile Instrument Co., Ltd. The drugs used in the experiment were purchased and used directly without any treatment.
[0032] Embodiment 1:
[0033] Core layer spinning solution preparation: Use a pipette to take 20 mL of chloroform and 30 mL of N,N-dimethylformamide respectively and add them to a 100 mL screw-mouth conical flask to obtain a mixed solvent with a volume ratio of TCM / DMF (4 / 6, v / v). Use an electronic analytical balance to weigh 1.0-2.0 g of PS particles and add them to a screw-mouth conical flask filled with TCM / DMF mixed solvent, add a magnetic rotor and tighten the bottle cap, where the concentration of the PS solution is 20% (w / v), place the conical flask on a magnetic stirrer at room temperature and stir for 24 hours to obtain a colorless and transparent solution.
[0034] Preparation of the intermediate layer spinning solution: Use a pipette to take 15 mL of chloroform and 35 mL of N,N-dimethylformamide respectively and add them to a 100 mL screw-mouth conical flask to obtain a mixed solvent with a volume ratio of TCM / DMF (3 / 7, v / v). Use an electronic analytical balance to weigh 1.0-1.2 g of PAA powder and add it to a screw-mouth conical flask filled with TCM / DMF mixed solvent, add a magnetic rotor and tighten the bottle cap, where the concentration of the PAA solution is 10% (w / v), place the conical flask on a magnetic stirrer at room temperature and stir for 24 hours to obtain a colorless and transparent solution.
[0035] Sheath spinning solution preparation: Use a pipette to take 40 mL of chloroform and 10 mL of N,N-dimethylformamide and add them to a 100 mL screw-mouth conical flask to obtain a mixed solvent with a volume ratio of TCM / DMF (8 / 2, v / v). Use an electronic analytical balance to weigh 1.0-1.2 g of PCL particles and add them to a screw-mouth conical flask filled with TCM / DMF mixed solvent. Add a magnetic rotor and tighten the cap. The concentration of the PCL solution is 10% (w / v). Place the conical flask on a magnetic stirrer at room temperature and stir for 24 hours to obtain a colorless and transparent solution.
[0036] Electrospinning: The prepared spinning solution was carefully placed into 20mL, 10mL, and 10mL syringes according to the core layer spinning solution, the middle layer spinning solution, and the sheath layer spinning solution, and placed on the micro-injection pump. The high-voltage electrostatic box and the homemade improved coaxial spinning head were connected with an alligator clip. Under the condition of ensuring grounding, a cardboard box wrapped with aluminum foil was used as the receiving device for the fiber in the experiment. The spinning parameters were set as follows: spinning voltage 8.2kV, core layer spinning solution flow rate 1.2mL / h, middle layer spinning solution flow rate 0.5mL / h, sheath layer spinning solution flow rate 0.8mL / h, receiving distance 18cm, and a nanofiber membrane with super water absorption performance was obtained after spinning for a period of time.
[0037] After collecting the prepared fiber membrane with aluminum foil, it was placed in a 40°C constant temperature oven for 12 hours to completely evaporate the solvent, and then the sample was sealed in a drying dish with a plastic bag. During spinning, a copper mesh was used to receive the nanofibers for 3-5 seconds. After the nanofibers were processed, the microscopic morphology of the samples was characterized by transmission electron microscopy (TEM). Figure 2 This is a transmission electron microscope (TEM) image of super absorbent core-sheath structure nanofibers. The fibers have a distinct core-sheath structure.
[0038] Take the dried nanofiber membrane, cut it into 10mm×10mm square and weigh the dry weight on an electronic analytical balance. Take a 100mL beaker and add 80mL deionized water. Immerse the cut nanofiber membrane completely in deionized water. Take it out every 5 minutes until there is no water droplet, then weigh and record. The recorded data is processed by Origin Pro2023 to obtain the water absorption performance of the super absorbent nanofiber membrane. The maximum amount of liquid absorbed is 550% of its own weight. Figure 3 shown.
[0039] Result analysis:
[0040] 1) Preparation of super absorbent nanofiber membrane with core-sheath structure by three-stage coaxial electrospinning process
[0041] A three-stage coaxial electrospinning process was used to prepare a super absorbent nanofiber membrane with a core-sheath nanofiber structure, using a TCM / DMF solution of polycaprolactone as the sheath spinning solution, a TCM / DMF solution of polyacrylic acid as the middle layer spinning solution, and a TCM / DMF solution of polystyrene as the core layer spinning solution. This achieves the goal of maintaining the water absorption performance of the super absorbent fiber while maintaining the fiber shape, so that the fiber membrane still maintains a complete fiber membrane morphology after absorbing water and does not shrink into a ball.
[0042] 2) Transmission electron microscopy image of super absorbent nanofibers
[0043] The prepared electrospun super absorbent nanofibers have an obvious core-sheath structure. The fibers are mainly composed of a polystyrene layer that plays a supporting role, namely the core layer, a polyacrylic acid layer that plays a water-absorbing role, namely the middle layer, and a thinner polycaprolactone layer that plays a protective role, namely the sheath layer.
[0044] 3) Absorption performance of super absorbent nanofibers for deionized water
[0045] The prepared super absorbent fiber maintained rapid and stable water absorption capacity within the first 2 hours and reached a water absorption equilibrium state at 2 hours, with a maximum water absorption capacity of 550% of the fiber's own weight.
[0046] It should be noted that the polymers used in the core layer, the middle layer and the sheath layer in the present invention can be replaced by other suitable polymers, and the electrospinning method is not limited to three-stage coaxial electrospinning.
[0047] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any technician in the relevant technical field, without departing from the scope of the technical solution of the present invention, makes any form of equivalent replacement or modification to the technical solution and technical content disclosed in the present invention, which does not depart from the content of the technical solution of the present invention and still falls within the protection scope of the present invention.
Claims
1. A method for preparing super absorbent core-sheath structure nanofibers using three-stage coaxial electrospinning, characterized in that: The steps include: S1: 20 mL of chloroform and 30 mL of N,N-dimethylformamide were weighed and added to a first screw-mouth conical flask, and 1.0-2.0 g of dried polystyrene particles were weighed and added to the first screw-mouth conical flask, and finally stirred with a magnetic stirrer to obtain a clear, transparent and uniform first polymer solution, which was placed aside for use; S2: 15 mL of chloroform and 35 mL of N,N-dimethylformamide were weighed and added to a second screw-mouth conical flask, and 1.0-1.2 g of polyacrylic acid powder was weighed and added to the second screw-mouth conical flask, and finally stirred with a magnetic stirrer to obtain a clear, transparent and uniform second polymer solution; S3: 40 mL of chloroform and 10 mL of N,N-dimethylformamide were weighed and added to a third screw-mouth conical flask, and 1.0-1.2 g of polycaprolactone particles were weighed and added to the third screw-mouth conical flask, and finally stirred with a magnetic stirrer to obtain a clear, transparent and uniform third polymer solution; S4: A three-stage coaxial electrospinning process was used to collect 20 mL of the first polymer solution, 10 mL of the second polymer solution and 10 mL of the third polymer solution using a syringe, and the first polymer solution, the second polymer solution and the third polymer solution were placed in the propulsion pumps of the corresponding core layer, the middle layer and the sheath layer, respectively, and a cardboard box wrapped in aluminum foil was used as a receiver to spin and obtain nanofibers with super absorbency; In S1-S3, the magnetic rotor is placed in a screw-mouth conical flask, and the screw-mouth conical flask is placed on a magnetic stirrer for stirring for 24 hours; In S4, the electrospinning process is specifically as follows: connecting the positive electrode of the high-voltage power supply to the needle of the coaxial spinning head, connecting the negative electrode to the aluminum foil, setting the parameters of the spinning flow rate, the spinning voltage and the receiving distance, connecting the high-voltage power supply and spinning, and obtaining nanofibers with super water absorption; The spinning flow rates are specifically as follows: the core layer flow rate is set to 1.2 mL / h, the middle layer flow rate is set to 0.5 mL / h, and the sheath layer flow rate is set to 0.8 mL / h; the spinning voltage is 8.2 KV; and the receiving distance is 18 cm.
2. The method for preparing super absorbent core-sheath structure nanofibers according to claim 1, characterized in that: Super absorbent core-sheath structure nanofibers are prepared, wherein the core-sheath structure comprises a core layer, an intermediate layer and a sheath layer; The first polymer solution, the second polymer solution and the third polymer solution are used as solutions for the core layer, the middle layer and the sheath layer, respectively. In the prepared super absorbent core-sheath structure nanofibers, the middle layer made of polyacrylic acid has super absorbency and is used to absorb liquids. The core layer made of polystyrene is used to provide the required rigidity for the fiber and maintain the fiber morphology characteristics. The sheath layer made of polycaprolactone protects the fiber structure and prevents the middle layer from absorbing too much water and causing the fiber membrane to shrink into a ball.
Citation Information
Patent Citations
Preparation method of high-mechanical-property super-absorbent fiber
CN115595794A
Super water absorbent fiber
CN1664189A
Super-hydrophilic polymer microsphere and preparation method thereof and super-hydrophilic fabric prepared by preparation method
CN108342902A
Multi-layered microfibers and use thereof
US20180044817A1